2020
DOI: 10.47960/2303-8616.2020.12.105
|View full text |Cite
|
Sign up to set email alerts
|

Utjecaj Rekreacijskih Aktivnosti Na Mentalno Zdravlje

Abstract: Rekreacijska aktivnost je složen pojam i često je povezana s ostalim potencijalno korisnim elementima kao što su socijalna interakcija, izloženost svježem zraku, boravak u prirodi. Tjelesna aktivnost ima važnu ulogu u poboljšanju psihičkog zdravlja. Procesi kojima rekreacijska aktivnost utječe na opću dobrobit i mentalno zdravlje su veoma složeni. Zbog toga je jako teško odrediti element ponašanja i aktivnost koja će sa sigurnošću donijeti korist u bavljenju fizičkom aktivnosti.Poticanje na fizičku aktivnost n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In this sense, the role of serotonin is most often mentioned. Serotonin, among other neurotransmitters, participates in creating a good mood (Marić et al, 2020;Wipfli et al, 2011). The level or secretion of serotonin is influenced by numerous factors and regulatory mechanisms, and physical activity is definitely among them.…”
Section: Mechanisms Of Influence Of Physical Activity On Mental Healt...mentioning
confidence: 99%
See 3 more Smart Citations
“…In this sense, the role of serotonin is most often mentioned. Serotonin, among other neurotransmitters, participates in creating a good mood (Marić et al, 2020;Wipfli et al, 2011). The level or secretion of serotonin is influenced by numerous factors and regulatory mechanisms, and physical activity is definitely among them.…”
Section: Mechanisms Of Influence Of Physical Activity On Mental Healt...mentioning
confidence: 99%
“…The influence of physical activity on cognitive functioning et al, 2016). Many reviews showed that regular physical activity can lead to better brain functioning (Marić et al, 2020), and hence to improved cognitive and academic performance (Biddle & Asare, 2011).…”
Section: Mechanisms Of Influence Of Physical Activity On Mental Healt...mentioning
confidence: 99%
See 2 more Smart Citations
“…Marić i suradnici navode da je redovito vježbanje i bavljenje sportom pozitivno povezano sa samopoštovanjem i samopoimanjem, a negativno je povezano sa stresom, anksioznošću i depresijom. Fizička aktivnost i tjelovježba korisne su u promociji pozitivne fizičke samopercepcije neovisno o spolu i dobnoj skupini (34). Johnsgardi i suradnici (35) uočili su da je nakon dvadeset i jednog mjeseca programiranog bavljenja sportom znatno manja količinu simptoma stresa i depresije u grupi od petnaest pacijenata, nego li u kontrolnoj grupi koja nije bila podvrgnuta nikakvoj terapiji.…”
Section: Slika 2 Dobne Razlike Među Spolovimaunclassified